If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 7x + 2x = 15 Combine like terms: 7x + 2x = 9x 6 + 9x = 15 Solving 6 + 9x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 9x = 15 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = 15 + -6 9x = 15 + -6 Combine like terms: 15 + -6 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| 7.37=3.14(r) | | -9-11=68 | | f^2-4f=29 | | 4x-4/20 | | 3x-(-1)=-9 | | c=12n+5 | | -40(8-x)=4x+10 | | 6+6x=48 | | 1000=.290*W/.750^2 | | 19+1.25x=15+2.75x | | 3+y=10x | | (1/2)•x | | 65(103.0)=x(8) | | 1-2x=-19 | | d^2-22d=31 | | (1.50+4)=33.96 | | 1000=.290*W*/.750^2 | | -x+6-2x=0 | | u+4.74=6.65 | | 10y-26=24 | | Y-6=11+x | | -3x-16=-7(x-4) | | 2x+y^2-3x^2+x-y^2-3x= | | 5/2x-x=9 | | 4(-3x-10)=-64 | | 3n^3-4n^2-9n+12=0 | | A(65)=8(103.0) | | 5x+15(4)=35 | | p^2-20p+49=0 | | 2(5x-63)=-4x-14 | | 20x-40=15x+3 | | 6/7(3) |